The Effect of Entrepreneurship Education and Creativity on Students’ Entrepreneurial Intention : The Perspective of Effectuation and Cognitive Flexibility Theory - Atrup Atrup; Prety Diawati; Syamsuri Syamsuri; Susatyo Adhi Pramono; Abu Muna Almaududi Ausat (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This study aims to examine the impact of entrepreneurship education and creativity on students' entrepreneurial intention through the perspective of Effectuation Theory and Cognitive Flexibility Theory. The research used a quantitative approach to analyze structural equation modeling (SEM) and Partial Least Square (PLS). Respondents were drawn from 100 university students in Subang Regency, Indonesia, through an online questionnaire. The findings of this study showed positive and significant evidence between entrepreneurship education, creativity, and students' entrepreneurial intention. Through the Effectuation and Cognitive Flexibility Theory principles, students could develop the entrepreneurial attitude, adaptability, and creative thinking necessary to run their own businesses. Entrepreneurship education helps them understand business opportunities, utilize existing resources, and cope with uncertainty.